Antimicrobial activities of chili leaf, guava leaf and their combination with garlic bulb extract against foodborne microorganisms in spaghetti meat sauce - Martinez, Stephanie Jean D.
This study was conducted to establish the antimicrobial efficacies of ethanolic guava leaf- (EGE) and ethanolic chili leaf extract (ECE) and their co-supplementation with garlic bulb extract (GBE) against common foodborne microorganisms such as Escherichia coli O157:H7, Salmonella enterica serovars, Listeria monocytogenes, and Staphylococcus aureus. The maximum permissible supplementation (MPS) levels for EGE, ECE, and GBE in spaghetti with meat sauce were determined through consumer acceptability testing to be 2.5, 2.5, and 4.0%, respectively. The minimum inhibitory concentration (MIC) values for EGE and ECE were determined through agar dilution technique to be 8-10% and 8-9%, respectively; while previously reported MIC for GBE was 2.5%. These results showed that application of EGE and ECE MIC shall result in unacceptable spaghetti with meat sauce. Thus, the efficacies of EGE+GBE and ECE+GBE were established. Results showed that combining 3.0% GBE reduced EGE and ECE MIC values to 2.5%. These minimum inhibitory combination (MICo) values of 2.5% EGE+ 3.0% GBE and 2.5%ECE+ 3.0%GBE were applied in spaghetti with meat sauce samples that were not disliked by the consumer panel. These MICo values similarly exhibited bacteriostatic efficacies against resistant test organisms in artificially inoculated spaghetti meat sauce. The results of this study may be used in the improvement of the control of safety of spaghetti with meat sauce, which has been commonly associated with foodborne illnesses.